Ventral Midbrain NTS1 Receptors Mediate Conditioned Reward Induced by the Neurotensin Analog, D-Tyr[11]neurotensin - Rouibi, Khalil; Bose, Poulomee; Rompré, Pierre-Paul; Warren, Richard A. (Frontiers in Neuroscience, 2015)
The present study was aimed at characterizing the mechanisms by which neurotensin (NT) is acting within the ventral midbrain to induce a psychostimulant-like effect. In a first experiment, we determine which subtype(s) of NT receptors is involved in the reward-inducing effect of ventral midbrain microinjection of NT using the conditioned place-preference (CPP) paradigm. In a second study, we used in vitro patch clamp recording technique to characterize the NT receptor subtype(s) involved in the modulation of glutamatergic neurotransmission (excitatory post-synaptic current, EPSC) in ventral tegmental neurons that expressed (Ih+), or do not express (Ih-), a hyperpolarization-activated cationic current. Behavioral studies were performed with adult male Long-Evans rats while electrophysiological recordings were obtained from brain slices of rat pups aged between 14 and 21 days. Results show that bilateral ventral midbrain microinjections of 1.5 and 3 nmol of D-Tyr[11]NT induced a CPP that was respectively attenuated or blocked by co-injection with 1.2 nmol of the NTS1/NTS2 antagonist, SR142948, and the preferred NTS1 antagonist, SR48692. In electrophysiological experiments, D-Tyr[11]NT (0.01-0.5 M) attenuated glutamatergic EPSC in Ih+ but enhanced it in Ih- neurons. The attenuation effect (Ih+ neurons) was blocked by SR142948 (0.1 M) while the enhancement effect (Ih- neurons) was blocked by both antagonists (0.1 M). These findings suggest that i) NT is acting on ventral midbrain NTS1 receptors to induce a rewarding effect and ii) that this psychostimulant-like effect could be due to a direct action of NT on dopamine neurons and/or an enhancement of glutamatergic inputs to non-dopamine (Ih-) neurons.